Coactivator complexes participate in different stages of the Drosophila melanogaster hsp70 gene transcription. - Mazina, M.Yu.; Derevyanko, P.K.; Kocheryzhkina, E.V.; Nikolenko, Yu.V.; Krasnov, A.N.; Vorobyeva, N.E. (Russian Journal of Genetics (English translation edition of Genetika), 2017)
The objective of this study was to identify transcriptional coactivators participating in transcription elongation of the hsp70 gene induced by heat shock. We found that all investigated coactivator complexes participate in transcription of this gene, as significant level of them were present at the gene promoter in its active state. For most of the coactivators (except for p300/CBP, Set2, and Mediator complex), we also observed a considerable increase of their binding level at the coding region of the gene after activation of its transcription by heat shock. We assume that coactivators CHD1, ISWI, Brm, Kismet-L, INO80, Mi-2, Gcn5, Lid/KDM5, Set1, DART1, DART4, SSRP1, PAF1, and Fs(1)h/Brd4 bind to the promoter of the active hsp70 gene and migrate to its coding region together with elongating RNA polymerase II. It can be suggested that some of these coactivators play an important role in stimulating the transition of the RNA polymerase II complex from transcription initiation to elongation stage.